1996
DOI: 10.1021/ci9500905
|View full text |Cite
|
Sign up to set email alerts
|

Using New Reasoning Technology in Chemical Information Systems

Abstract: Unreliability of numerical data causes difficulties in computer systems for decision-making, risk assessment, and similar activities. Much human judgment is non-numerical and able to make useful evaluations of alternatives under uncertainty. The Logic of Argumentation (LA) offers a basis for computerized support of decision-making in the absence of numerical data, and it is being used in a project on carcinogenic risk assessment, StAR. There are potential applications of LA in other artificial intelligence sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Four lines of work on trust and argumentation that are complementary to ours include those of Harwood [38,39], Matt at al., Hunter [40], [58], and Stranders [84]. In addition, argumentation has been used in the past to reason about risk [47,60], a subject closely related to trust though the cited work looked at risk of carcinogenicity given chemical structure rather than risk due to untrustworthiness.…”
Section: Discussionmentioning
confidence: 99%
“…Four lines of work on trust and argumentation that are complementary to ours include those of Harwood [38,39], Matt at al., Hunter [40], [58], and Stranders [84]. In addition, argumentation has been used in the past to reason about risk [47,60], a subject closely related to trust though the cited work looked at risk of carcinogenicity given chemical structure rather than risk due to untrustworthiness.…”
Section: Discussionmentioning
confidence: 99%
“…For a detailed comparison of this work and ours, see [37]. In addition, argumentation has been used in the past to reason about risk [18,25], a subject closely related to trust; though the cited work looks at risk of carcinogenicity given chemical structure rather than risk due to untrustworthiness.…”
Section: Discussionmentioning
confidence: 99%
“…Here the work by Fox and colleagues [14,17] showed that constructing arguments for and against a decision option, and then simply combining these arguments 8 could provide a decision mechanism that rivalled the accuracy of probabilistic models. This basic method was extended in [18,51] to create a symbolic mechanism that, like classical decision theory, distinguished between belief in propositions and the values of decision outcomes, while [30] showed the usefulness of arguments in communicating evidence for decision options to human users. More recent work on argumentation and decision making is described in [31,71].…”
Section: Argumentation-based Decision Makingmentioning
confidence: 99%